THE SPECIFICS OF NATIONAL MORAL VALUES IN INCREASING THE EFFECTIVENESS OF INTIAL PRECONSCRIPTION TRAINING - Niyazov Numan Enverovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article provides information on the specifics of national moral values in increasing the effectiveness of intial preconscription training